An Unusual Etiology of Submandibular Sialadenitis, Migration of an Ingested Fish Bone to the Submandibular Gland: A Case Report (Faridpur Medical College Journal, 2021)
Recurrent sialadenitis of submandibular gland can have multiple causes, one of the rare being foreign bodies. Motor vehicle accidents, assaults, bullet wounds and iatrogenic surgical fault are the most common causes of traumatic foreign bodies. Fish bone is one of the most common foreign bodies that gets lodged in the upper digestive tract, often located in the tonsil, base of tongue, epiglottis, pyriform fossa and esophagus, where it may be easily identified on routine inspection and removed. The forcible swallowing of food such as rice balls after ingesting fish bones by mistake may lead to the migration of the fish bone from the pharynx, throat or esophagus to the surrounding tissues. Migration most commonly occurs to the soft tissues of the neck, even to the thyroid gland, but migration to the submandibular gland has rarely been reported. Here, we present a case of submandibular sialadenitis due to unusual migration of ingested fish bone to submandibular gland. Foreign body ingestion may cause a series of complications and endanger a patient's life. Cases require high awareness and attentiveness on the part of the first physician to diagnose and manage the condition and appropriate health education should be imparted to the patient.Faridpur Med. Coll. J. 2021;16(1):55-57